Understanding the relations between soil organic matter fractions and N2O emissions in a long‐term integrated crop–livestock system. (23rd May 2019) - Sato, Juliana Hiromi; de Figueiredo, Cícero Célio; Marchão, Robélio Leandro; de Oliveira, Alexsandra Duarte; Vilela, Lourival; Delvico, Francisco Marcos; Alves, Bruno José Rodrigues; de Carvalho, Arminda Moreira
Abstract: The nitrous oxide (N2 O) emissions in agricultural systems are influenced by edaphoclimatic conditions, and the availability of soil organic matter (SOM) is a key factor. The objective of this study was to evaluate the accumulation of labile and stable SOM fractions and possible relations with N2 O emissions using a multivariate approach in a 24‐year integrated crop–livestock experiment in the Cerrado region. The management systems consisted of: continuous cropping under no tillage (CC‐NT), continuous cropping under annual heavy disc harrow (CC‐CT), an integrated crop–livestock system under no tillage (CLS‐NT) and an adjacent area of native Cerrado as reference. The cumulative N2 O emissions were quantified over a period of 146 days throughout the cultivation of sorghum ( Sorghum bicolor (L.) Moench). Labile and stable soil carbon (C) fractions and C contents in classes of aggregates (macroaggregates >0.250 mm and microaggregates <0.250 mm) were determined. The cumulative N2 O emissions were larger in the CC‐CT system, intermediate in the CC‐NT and CLS‐NT systems, and smaller in the Cerrado. The decomposition of crop residues during the crop succession (first and second crop seasons) and the presence of a grass forage (with grazing and not grazed) in both systems (CLS‐NT and CC‐NT, respectively) explain the differences in N2 O fluxes between the land uses. Smaller cumulative N2 O emissions were observed in the integrated system (CLS‐NT), which could be attributed to the greatest increase in soil C in its most stable SOM fractions (fulvic acid) and occlusion in microaggregates. This confirms the hypothesis that the accumulation of C in the most stable SOM fractions of the soil, unavailable to the microbiota, results in smaller N2 O emissions. Principal component analysis also revealed that aggregation is a key attribute that correlates with soil N2 O emissions. Thus, conservation systems such as CLS‐NT had larger average diameter of aggregates and the smallest N2 O emissions among the agroecosystems. Highlights: Relations between SOM fractions and N2 O emissions were studied in integrated systems The accumulation of stabilized C fractions reduces N2 O emissions Soil structure (aggregation) and SOM stability partially explain N2 O fluxes Integrated crop–livestock promotes better soil conditions, reducing N2 O emissions